Seismic and hydroacoustic observations from recent underwater events in the South Atlantic Ocean. Issue 1 (20th July 2020) - Heyburn, Ross; Bowers, David; N. Green, David
SUMMARY: To study the location and characterize two underwater events in the South Atlantic Ocean, we analyse both seismic and hydroacoustic signals. The first event (2017 November 15) occurred around 550 km east of Argentina, near the last reported position of the Argentine Navy submarine the ARA San Juan, the seafloor wreck of which was found one year later. The second event (2017 December 1) was due to an aircraft-dropped depth charge, detonated as part of the search for the ARA San Juan. We use signal arrival times and azimuths recorded at two seismic and two hydroacoustic stations to estimate epicentres for both events; our estimates were within 10 km of the ground-truth locations. We used geophysical models and databases to determine the sound-speed structure of the water and the presence of sea-ice to help interpret differences in the frequency content and dispersion of signals at the two hydrophone stations. Hydrophone signals for the 2017 November 15 event contain significant energy at high frequencies, which is inconsistent with an earthquake source. Hydrophone signals for the 2017 December 1 event show frequency modulations consistent with those expected from the known depth and explosive energy. Hydrophone signals from the 2017 November 15 event also show frequency modulations, though differences between these for the two events suggest differences in the details of the source mechanisms. Using estimates of the local seismic magnitudes, the peak pressures recorded on the hydrophones, and the known charge weight for the 2017 December 1 event, we estimate that the 2017 November 15 event had an acoustic energy release equivalent to around 428 kg of trinitrotoluene. This analysis demonstrates the importance of high-precision traveltime predictions from models of seismic and ocean acoustic velocities when analysing low-magnitude underwater events.